Fiber manipulation and post-assembly nanobody conjugation for adenoviral vector retargeting through SpyTag-SpyCatcher protein ligation - Kadkhodazadeh, Maryam; Mohajel, Nasir; Behdani, Mahdi; Baesi, Kazem; Khodaei, Behzad; Azadmanesh, Kayhan; Arashkia, Arash (Frontiers in Molecular Biosciences, 2022)
For adenoviruses (Ads) to be optimally effective in cancer theranostics, they need to be retargeted toward target cells and lose their natural tropism. Typically, this is accomplished by either engineering fiber proteins and/or employing bispecific adapters, capable of bonding Ad fibers and tumor antigen receptors. This study aimed to present a simple and versatile method for generating Ad-based bionanoparticles specific to target cells, using the SpyTag-SpyCatcher system. The SpyTag peptide was inserted into the HI loop of fiber-knob protein, which could act as a covalent anchoring site for a targeting moiety fused to a truncated SpyCatcher (SpyCatcherΔ) pair. After confirming the presence and functionality of SpyTag on the Ad type-5 (Ad5) fiber knob, an adapter molecule, comprising of SpyCatcherΔ fused to an anti-vascular endothelial growth factor receptor 2 (VEGFR2) nanobody, was recombinantly expressed in Escherichia coli and purified before conjugation to fiber-modified Ad5 (fmAd5). After evaluating fmAd5 detargeting from its primary coxsackie and adenovirus receptor (CAR), the nanobody-decorated fmAd5 could be efficiently retargeted to VEGFR2-expressing 293/KDR and human umbilical vein endothelial (HUVEC) cell lines. In conclusion, a plug-and-play platform was described in this study for detargeting and retargeting Ad5 through the SpyTag-SpyCatcher system, which could be potentially applied to generate tailored bionanoparticles for a broad range of specific targets; therefore, it can be introduced as a promising approach in cancer nanotheranostics.